The periodic table - Faust, Daniel R. (Bearport Publishing Company, 2023)
"With elements all around, how can students-or even scientists-keep them straight? That's where the periodic table comes into play. Learn all about the way the table is organized, the different types of elements you can find on it, and more. It's key chemistry curriculum made approachable for all!"--
Finding What You Need -- A Chemical Library -- Looking Inside -- What's in the Box? -- Across and Down -- Mostly Metal -- Nonmetals and Metalloids -- Always Room for More -- Infographic -- SilverTips for Success.
Includes bibliographical references and index.
Keywords: Chemical elements -- Juvenile literature; Periodic table of the elements -- Juvenile literature